Antecedents of career aspiration of R&D professionals in Malaysian Public Organizations - Ramly, Efizah Sofiah; Ismail, Maimunah; Uli, Jegak (EuroJournals Publishing, Inc., 2009)
The paper analysed factors that influence R&D professionals’ career aspirations in Malaysian public organizations. The study used Schein’s Career Anchor Theory and Social Cognitive Career Theory (SCCT). The former describes the components that make up career aspirations, while the latter explains the cognitive-person variables (e.g. selfefficacy), external environment factors (e.g. organizational socialization) and behaviour (e.g. continuous improvement practices) in influencing career aspirations. The results were gathered from 158 R&D professionals of ten government research organizations in Malaysia through a survey research design. The data were analysed using descriptive statistics, Pearson Product-Moment correlation and multiple linear regressions. The results indicated that the three factors, namely, self-efficacy, organizational socialization and continuous improvement practices showed low positive linear relationships with the respondents’ career aspirations. However, the results showed that self-efficacy and continuous improvement practices were found to be the main contributors to explain variations in career aspiration.